Inhibition of TLR4 mitigates sensorineural hearing loss resulting from cochlear inflammation - Jintao Lou; Fan Wu; Wei Liu; Rui Hu; Wuhui He; Yisi Feng; Yan Huang; Jia Guo; Jingman Deng; Zhen Zhao; Zhigang Zhang; Yu Si (Molecular Medicine)
Abstract Background Inflammation is a principal cause of sensorineural hearing loss resulting from cochlear injury. However, current research investigating the mechanisms of sensorineural inflammatory injury remains inadequate. Methods Cochlear inflammation was induced by administering lipopolysaccharide (LPS) into the otic bulla (OB) and posterior semicircular canal (PSCC). Auditory brainstem responses (ABR) were recorded, and cochlear tissue alterations were analyzed using hematoxylin and eosin (HE) staining and immunofluorescence. Levels of cochlear inflammation were quantified using a cytokine array. Additionally, Toll-like receptor 4 (TLR4) knockout mice were employed to evaluate sensorineural neuroprotection. Results LPS injection into the PSCC caused more pronounced and stable cochlear inflammatory damage compared to injection into the OB. LPS exposure led to significant loss of cochlear hair cells, atrophy of the stria vascularis, and spiral ganglion damage. Furthermore, LPS treatment upregulated TLR4 receptor expression, increased the number of Ionized calcium-binding adapter molecule 1 (IBA1) positive cells, and elevated levels of inflammatory cytokines in the cochlea. TLR4 knockout (TLR4-KO) mice demonstrated reduced LPS-induced cochlear sensorineural damage. Conclusion LPS injection into the PSCC induces sensorineural tissue damage in the cochlea and results in sensorineural hearing loss. These findings suggest that TLR4 inhibition can alleviate cochlear inflammation-induced sensorineural hearing loss. TLR4 represents a potential therapeutic target for sensorineural hearing loss.